Development of crack propagation monitoring by vibration measurementpart one: at the end of the plate. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fac. of Geography Gadjah Mada Univ., 2001)
This investigation was undertaken to study both experimentally and numerically the longitudinal displacement amplitude behavior of plates containing a crack subjected to cyclic loads (fatigue crack growth rate test), with various load range. In this work, plates with a single edge crack were used. Those plates were subjected to various combination of stress levels (SL) and stress ratios ( R), namely: 10 % 6ys â 0,1, 15 % ays â 0,1, 15 % ay, â 0,2, 15 % ays - 0,3, and 18 % ays -0,1. An accelerometer was used to measure the longitudinal displacement amplitude at the end of the plate. This accelerometer was installed at the lower chuck of the test machine. Data acquisition was done by measuring the longitudinal displacement amplitude at specific crack length, as well as by counting the cycles. The results were then confirmed by comparing them with the results from the finite element analysis. The experimental results show that the increase of crack length (a/w) from 0,193 to 0,524 can increase the accelerometer's longitudinal displacement amplitude to 1,38 times. The change of the load range from 432 kg to 774 kg can increase the longitudinal displacement amplitude at the end of the plate to 1,77 times. The vibration measurement at the end of the plate has a good agreement with the finite element simulation, in which the longitudinal displacement amplitude deviation is less than 6 %.